2017
DOI: 10.1017/s136898001700297x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of infant and young child complementary feeding practices in South Asian families: the India perspective

Abstract: This is the first systematic review to evaluate CF practices in SA in India. Campaigns to change health and nutrition behaviour and revision of nationwide child health nutrition programmes are needed to meet the substantial unmet needs of these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 64 publications
(347 reference statements)
2
48
0
2
Order By: Relevance
“…The present review (PROSPERO registration number CRD42014014025) summarizes publications on CFP in SA families in Pakistan only, with concurrent reviews summarizing publications on CFP in SA families in India ( 18 ) , Bangladesh ( 19 ) and high-income countries (L Manikam, R Lingam, I Lever et al ., unpublished results), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The present review (PROSPERO registration number CRD42014014025) summarizes publications on CFP in SA families in Pakistan only, with concurrent reviews summarizing publications on CFP in SA families in India ( 18 ) , Bangladesh ( 19 ) and high-income countries (L Manikam, R Lingam, I Lever et al ., unpublished results), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…About one-fifth of mother practiced MAD among their children, having no knowledge of child feeding might be due to the association of knowledge on child feeding with MAD. The evidence from systematic review showed that lack of knowledge was a key barriers of optimal complementary feeding practice [37]. In Nepal, a study showed the inadequate minimum acceptable diet practices would be due to poor knowledge on child feeding practices [19].…”
Section: Discussionmentioning
confidence: 99%
“…Other papers published by our group as part of this project reviewed CF practices in Bangladesh, Pakistan, and India [ 16 , 17 , 18 ]. As reported in this review, the most common CF food groups for SA infants in high-income countries were “fruits and vegetables”, “flesh foods” and “dairy products”, described by six studies each, whereas the other reviews found “Grains, roots and tubers” were most commonly used for CF in the SA countries themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This left 978 potentially eligible full text articles, which were independently reviewed by two researchers. One hundred and thirty-nine full text articles were ultimately extracted, of which 13 were relevant to high-income countries and the remainder relevant to India, Bangladesh and Pakistan [ 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation